Social media use and mental health of urban residents during China's second COVID-19 outbreak - Zheng, Zhenhua; Sun, Ning; Chen, Yu; Chen, Hong (Frontiers in Public Health, 2022)
Background: A multitude of literature has shown that during the 2019 COVID-19 outbreak, people’s reliance on social media has been closely related with serious psychological problems. The “information epidemic” has sparked each country’s attention. These countries including China have tried to find the solution and taken a series of measures. In January 2021, the COVID-19 broke out again in Shijiazhuang, China. Has the impact of social media on mental health changed? Methods: Our data are based on an online survey of Chinese in January 2021, with 904 valid samples from 18 different provinces in China. We applied the methods of structural equation model analysis and the tendency value matching to conduct systematic analysis. Results: Our research found that 38.9% of the population suffered from depression and 12.61% of the population suffered from anxiety. Chinese urban residents are more dependent on social media, with up to 80.1% of participants using social media frequently. Our research found that the relationship between social media use and residents’ mental health has dramatically changed. More use of social media has been significantly associated with less depression and anxiety, especially among young people and women. Our findings are the first to reveal the relation’s change between social media and mental health. Conclusions: These findings implied that changes in the social media environment probably lead to changes in relationship between social media use and mental health since the outbreak began in 2019. Truthful and comprehensive social media information and a healthy positive social media environment can contribute to residents' mental health improvement and the fight against "information epidemic"